Having a memory of an elephant: artistic and political approaches to not forget the brazilian military dictatorship - D’Avila Junior, Francisco de Paulo (Revista Binacional Brasil-Argentina: Dialogue between the sciences, 2024)
This article seeks to investigate how it is possible, through art, to cultivate a culture and politics of memory, given the horrors established by the dictatorial regime imposed by the 1964 Coup in Brazil. Unlike other countries in Latin America, where there is an effort to preserve memories about Military Dictatorships, in Brazil there is an absence of this type of debate, and little effort to maintain these memories, mainly on the part of the Brazilian State. In this sense, how can art contribute? To write this text, works by the Argentine artist Gustavo Germano and the Brazilian theater group Ói Nóis Aqui Traveiz were analyzed. In addition to a discussion about memory based on the ideas of German researcher and professor Andreas Huyssen.